PROBLEMATIKA PEMBELAJARAN PAI BERBASIS MULTIKULTURAL - Baehaqi, Sirojul; Rakhmawati, Rakhmawati; Ramidi, Ramidi; Purwoko, Purwoko (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study examines the role of education in shaping social change and fostering human values ??amidst Indonesia's cultural diversity that is vulnerable to homogenization. The national education law is committed to producing knowledgeable, moral, and democratic citizens. Therefore, multicultural education is urgently needed, integrating human rights and cultural diversity into the curriculum. Islamic Religious Education (PAI) plays an important role in shaping moral and tolerant individuals, but faces challenges such as perspective bias. It is important for PAI to promote tolerance and respect through effective multicultural teaching methodologies. This descriptive qualitative study analyzes the literature, identifying three core areas: inclusive pedagogy, teacher cultural competence, and dialogue facilitation. Recommendations are provided for the effective implementation of PAI in an inclusive and harmonious school environment, affirming the relationship between diversity and unity in nation building through education. ABSTRAKPenelitian ini mengkaji peran pendidikan dalam membentuk perubahan sosial dan menumbuhkan nilai kemanusiaan di tengah keberagaman budaya Indonesia yang rentan terhadap homogenisasi. Undang-undang pendidikan nasional berkomitmen mencetak warga negara berpengetahuan, bermoral, dan demokratis. Oleh karena itu, pendidikan multikultural mendesak dibutuhkan, mengintegrasikan hak asasi manusia dan keragaman budaya ke dalam kurikulum. Pendidikan Agama Islam (PAI) berperan penting dalam membentuk individu bermoral dan toleran, namun menghadapi tantangan seperti bias perspektif. Penting bagi PAI untuk mempromosikan toleransi dan rasa hormat melalui metodologi pengajaran multikultural yang efektif. Studi kualitatif deskriptif ini menganalisis literatur, mengidentifikasi tiga area inti: pedagogi inklusif, kompetensi budaya guru, dan fasilitasi dialog. Rekomendasi diberikan untuk implementasi PAI yang efektif dalam lingkungan sekolah yang inklusif dan harmonis, menegaskan hubungan keragaman dan persatuan dalam pembangunan bangsa melalui pendidikan.